Highly Emissive Organic Single‐Molecule White Emitters by Engineering o‐Carborane‐Based Luminophores. Issue 38 (9th August 2017) - Tu, Deshuang; Leong, Pakkin; Guo, Song; Yan, Hong; Lu, Changsheng; Zhao, Qiang
Abstract: The development of organic single‐molecule solid‐state white emitters holds a great promise for advanced lighting and display applications. Highly emissive single‐molecule white emitters were achieved by the design and synthesis of a series of o ‐carborane‐based luminophores. These luminophores are able to induce multiple emissions to directly emit high‐purity white light in solid state. By tuning both molecular and aggregate structures, a significantly improved white‐light efficiency has been realized (absolute quantum yield 67 %), which is the highest value among the known organic single‐molecule white emitters in the solid state. The fine‐tuning of the packing modes from H‐ to J‐ and cross‐stacking aggregates as well as intermolecular hydrogen bonds are successful in one molecular skeleton. These are crucial for highly emissive white‐light emission in the solid state. Abstract : By tailoring the molecular and aggregate structures of o ‐carborane‐based luminophores, crystal packing modes can be tuned, leading to a white‐light luminous efficiency up to 67 % in the solid state. These luminophores are able to induce multiple emissions to directly emit high‐purity white light. LE=locally excited, CT=charge transfer, PL=photoluminescence.